Noryang : Deadly sea [videorecording (DVD)] - Kim, Han-min, 1969-; Lee, Na-ra; Yoon, Hong-ki; Kim, Yun-sŏk, 1968-; Baek, Yoon-sik; Jung, Jae-young, 1970- (Well Go USA Entertainment, 2024)
Legendary Admiral Yi leads an allied fleet of ships against invaders in his final valiant naval battle to annihilate the retreating Japanese army. Now seven years after their deadly invasions of Korea, a massive battle at sea unfolds during the winter of 1598 in the Noryang Strait.